The response to Typhi Vi vaccination is compromised in individuals with primary immunodeficiency. Issue 6 (June 2017) - Kumarage, Jeevani; Seneviratne, Suranjith L.; Senaratne, Vijitha; Fernando, Amitha; Gunasekera, Kirthi; Gunasena, Bandu; Gurugama, Padmalal; Peiris, Sudath; Parker, Antony R.; Harding, Stephen; de Silva, Nilhan Rajiva
Abstract: Measurement of an individuals ability to respond to polysaccharide antigens is a crucial test to determine adaptive immunity. Currently the response to Pneumovax ® is utilized but with the success of Prevnar ®, measurement of the response to Pneumovax may be challenging. The aim of the study was to assess the response to Typhi Vi vaccination in both children and adult control groups and patients with primary immunodeficiency (PID). In the control groups, >95% of the individuals had pre Typhi Vi vaccination concentrations <100 U/mL and there was significant increase in concentration post Typhi Vi vaccination (p<0.0001) with>94% achieving ≥3 fold increase in concentration (FI). The response to Typhi Vi vaccination was significantly lower in both children ( p = 0.006) and adult ( p = 0.002) PID groups when compared to their control groups. 11% and 55% of the children and adult PID groups respectively did not obtain a response >3FI. There were no significant differences between the responses obtained in the children and adult PID groups. When all individuals with PID were separated into those with either hypogammaglobulinemia (HYPO) or common variable immunodeficiency (CVID), both groups had a significantly lower median FI than the control group (19, 95%CI 5–56 vs 59, 95%CI 7–237; p = 0.01 and 1, 95%CI 1–56 vs 32, 95%CI 5–136; p = 0.005). Further, a >3FI differentiated the antibody responses between both the CVID and HYPO groups and their control groups (AUC: 0.83, 95%CI: 0.65–1.00, p = 0.005 and 0.81, 95% CI: 0.65–0.97, p = 0.01). The data suggests that measurement of the response to Typhi Vi vaccination could represent a complementary assay for the assessment of the response to a polysaccharide vaccine.